Technology-enhanced multi-domain at home continuum of care program with respect to usual care for people with cognitive impairment: the Ability-TelerehABILITation study protocol for a randomized controlled trial. Issue 1 (December 2016) - Realdon, O.; Rossetto, F.; Nalin, M.; Baroni, I.; Cabinio, M.; Fioravanti, R.; Saibene, F.; Alberoni, M.; Mantovani, F.; Romano, M.; Nemni, R.; Baglio, F.
Abstract Background According to the World Alzheimer Report (Prince, The Global Impact of Dementia: an Analysis of Prevalence, Incidence, Cost and Trends, 2015), 46.8 million people worldwide are nowadays living with dementia. And this number is estimated to approximate 131.5 million by 2050, with an increasing burden on society and families. The lack of medical treatments able to stop or slow down the course of the disease has moved the focus of interest toward thenonpharmacological approach andpsychosocial therapies for people with/at risk of dementia, as in the Mild Cognitive Impairment (MCI) condition. The purpose of the present study is to test an individualized home-based multidimensional program aimed at enhancing the continuum of care for MCI and outpatients with dementia in early stage using technology. Methods The proposed study is a single blind randomized controlled trial (RCT) involving 30 subjects with MCI and Alzheimer's disease (AD) randomly assigned to the intervention group (Ability group), who will receive the "Ability Program", or to the active control group (ACG), who will receive "Treatment As Usual" (TAU). The protocol provides for three steps of assessment: at the baseline (T_0), after treatment, (T_1) and at follow-up (T_2) with a multidimensional evaluation battery including cognitive functioning, behavioral, functional, and quality of life measures. The Ability Program lasts 6 weeks, comprises tablet-delivered cognitive (5 days/week) and physical activities (7 days/week) combined with a set of devices for the measurement and monitoring from remote of vital and physical health parameters. The TAU equally lasts 6 weeks and includes paper and pencil cognitive activities (5 days/week), with clinician's prescription to perform physical exercise every day and to monitor selected vital parameters. Discussion Results of this study will inform on the efficacy of a technology-enhanced home care service to preserve cognitive and motor levels of functioning in MCI and AD, in order to slow down their loss of autonomy in daily life. The expected outcome is to ensure the continuity of care from clinical practice to the patient's home, enabling also cost effectiveness and the empowerment of patient and caregiver in the care process, positively impacting on their quality of life. Trial registration ClinicalTrials.gov ID:NCT02746484 (registration date: 12/apr/2016 – retrospectively registered).